Pemetaan Distribusi Ekosistem Mangrove di Wilayah Kota Surabaya dan Sidoarjo Memanfaatkan Citra Landsat TM-5 [Distribution Mapping of Mangrove Ecosystem in Surabaya and Sidoarjo by Using Landsat TM-5 Imagery] - Zainul Hidayah (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
Abstract Rapid developments on the coastal regions have become a major thread to mangrove ecosystems. The conversion of mangrove forest into fish ponds, housing and industrial sites make the area of this unique tropical ecosystem decline significantly in the last decade. To prevent further destruction of mangrove ecosystems due to human activities, conservation programs are needed. Therefore, information on mangrove's area as well as their distribution is needed. The main objective of this research was to demonstrate the ability of remote sensing and geographic information technology to provide reliable and accurate data on mangrove forest in Surabaya and thSidoarjo regions. A Landsat TM-5 imagery (acquisition date June 4 , 2009) data was utilized to produce the map. The results showed that in the 2009 period the area of mangrove forest in Surabaya and Sidoarjo was 378.19 Ha and 1236.42 Ha respectively. However, over 73.5% area of mangrove in Surabaya and 43.25% in Surabaya were under critical conditions. Anthropogenic factors and human influence were some of the main factors that cause the condition. Activities such as illegal and uncontrolled logging, conversion of mangrove's area and the lack of people's awareness in the importance of mangrove ecosystems were also problems that lead to the massive damage of mangrove forests.